1995
DOI: 10.1021/bi00049a030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Oxidatively Damaged Adduct 8-Oxodeoxyguanosine on the Conformation, Energetics, and Thermodynamic Stability of a DNA Duplex

Abstract: As part of an overall program to characterize the impact of mutagenic lesions on the physiochemical properties of DNA, we report here the results of a comparative spectroscopic and calorimetric study on a family of DNA duplexes both with and without the oxidative lesion 2'-deoxy-7-hydro-8-oxoguanosine (8-oxodG). Specifically, we have studied a family of eight 13-mer duplexes of the form [5'-GCGTAC[G* or G]CATGCG-3'].[3'-CGCATG[C, A, T, or G]GTACGC-5'] in which G* is the 8-oxodG lesion. These eight duplexes, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
227
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(281 citation statements)
references
References 54 publications
49
227
4
Order By: Relevance
“…These results are consistent with previous thermodynamic results as well as NMR and X-ray crystal structure studies (50)(51)(52), which showed that 8-oxodG can form base pairs with both dC and dA, depending on whether the damaged nucleoside adopts an anti or syn configuration about the glycosidic bond (50,51).…”
Section: Thermodynamic Studiessupporting
confidence: 93%
“…These results are consistent with previous thermodynamic results as well as NMR and X-ray crystal structure studies (50)(51)(52), which showed that 8-oxodG can form base pairs with both dC and dA, depending on whether the damaged nucleoside adopts an anti or syn configuration about the glycosidic bond (50,51).…”
Section: Thermodynamic Studiessupporting
confidence: 93%
“…It is believed that the presence of 8-hydroxy-2'-deoxyguanosine in urine reflects DNA repair processes taking place in the body. 31,32,35 Correlations between the amount of 8-OHdG in urine with the amount in tissues in different pathogenic processes are still being investigated. Undoubtedly, the greatest interest is in the correlation between the amount of 8-hydroxy-2'-deoxyguanosine and cancer, which can be explained by the mutagenic properties of 8-OHdG -namely, its ability to disrupt pairing rules in DNA transversion.…”
Section: -Hydroxy-2'-deoxyguanosinementioning
confidence: 99%
“…The general affinity for destabilized DNA sites may facilitate other excision repair processes, as XPC has been shown to interact with 3-methyladenine DNA glycosylase [49], thymine DNA glycosylase [50] and 8-oxoguanine DNA glycosylase [6]. It is relevant to note that even a subtle 8-oxoguanine lesion perturbs the thermodynamic stability of the duplex [51]. Accordingly, the XPC complex may provide a molecular platform not only for the loading of GGR players onto damaged DNA, but also for the recruitment of a battery of enzymes involved in base excision or other repair pathways.…”
Section: The Molecular Basis For Substrate Versatilitymentioning
confidence: 99%